Population and species boundaries in the South American subterranean rodent Ctenomys in a dynamic environment - Mirol, Patricia Monica (2010)
Subterranean rodents of the genus Ctenomys are an interesting system to assess the effects of habitat instability on the genetic structure of populations. The perrensi group is a complex of three species (C. roigi, C. perrensi and C. dorbignyi) and several forms of uncertain taxonomic status, distributed in the vicinity of the Iberá wetland in Argentina. Because of limited availability of suitable dry habitat, Ctenomys populations are distributed patchily around a vast mosaic of marshes, swamps and lagoons and become connected or isolated over time, depending particularly on the precipitation regime. Genetic variation at 16 microsatellite loci in 169 individuals collected in the area revealed eight clusters of populations which are thought to be evolutionary units, but which do not fit previous species limits. We interpret this lack of congruence between taxonomy and genetic structure as the result of a dynamic population structure. Where populations become connected, hybridization is possible. Where populations become isolated, rapid genetic divergence may occur. In the perrensi group, it appears that both of these factors disrupt the association between different genetic and morphological characters. The study of multiple characters is crucial to the understanding of the recent evolutionary history for dynamic systems such as this.